2020
DOI: 10.4314/jsasa.v53i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening public sector records management through the Information Regulator in South Africa

Abstract: The Information Regulator in South Africa is charged with the responsibility to regulate access to information. The implementation of the access to information legislation is heavily dependent on proper records management in the public sector; however, there is consensus among researchers that records are poorly managed in the public sector. The purpose of the study is to describe how records management in the public sector in South Africa can be strengthened through the Information Regulator. This qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These issues are faced in the communities where they stay and in the education environment. A study conducted by the South African Human Rights Commission (SAHRC) in 2017 found that 30% of female students had experienced sexual harassment, while 4% had experienced rape or attempted rape in the higher education sector (Mojapelo & Ngoepe, 2017). The study also revealed that only 4% of the victims had reported the incidents to college authorities.…”
Section: Background Literaturementioning
confidence: 99%
“…These issues are faced in the communities where they stay and in the education environment. A study conducted by the South African Human Rights Commission (SAHRC) in 2017 found that 30% of female students had experienced sexual harassment, while 4% had experienced rape or attempted rape in the higher education sector (Mojapelo & Ngoepe, 2017). The study also revealed that only 4% of the victims had reported the incidents to college authorities.…”
Section: Background Literaturementioning
confidence: 99%
“…The social invisibility of the public archives continues to be one of the barriers preventing members of the public exercising their right of access to public information (Mojapelo and Ngoepe, 2017), mainly because little effort is made to educate the people on what the NARSSA offers and the value of these records. Archival buildings are typically located at places that are far from the cities (Ngoepe and Ngulube, 2011); hence, it becomes difficult for people to even know about their existence.…”
Section: Literature Reviewmentioning
confidence: 99%